The Role of Corporate Governance in Sustainability of Malaysian NGOs Operated Elderly Care Centres - Shafi Mohamad; N. Fadzlyn; Abdullah Abdulaziz Bawazir; Nik Hasfizul Hassan (International Review of Management and Marketing)
Over recent years, the issue of sustainability has become a popular term in the research arena and policies. It appears that one of the best strategies to ensure sustainability of NGOs is through effective corporate governance. This exploratory study was conducted to identify the role played by corporate governance mechanisms in the sustainability of elderly care centres operated by Malaysian NGOs. This study adopted a semi-structured interview technique to achieve a better and more in-depth understanding. Ten (10) elderly care centres operated by NGOs in Kuala Lumpur and Selangor; Malaysia participated in this study. The findings indicated that corporate governance practices played a significant role in improving the sustainability of Malaysian elderly care centres run by NGOs and it was critical for these organisations to assess the corporate governance practices they employ in the management of their day-to-day operations to achieve better performance. This study can provide guidance to regulators in enhancing their regulatory framework so that it is more in line with the systems adopted by NGOs in other more developed countries. This study also recommended that boards of NGOs adopt corporate governance best practices to enhance the sustainability of their organisations.